Vibration suppression control of free-floating space robots with flexible appendages for autonomous target capturing. (October 2018) - Meng, Deshan; Lu, Weining; Xu, Wenfu; She, Yu; Wang, Xueqian; Liang, Bin; Yuan, Bo
Abstract: Some flexible appendages, such as solar panels, communication antenna and other large structures are mounted on the base of the space robot. The structure flexibilities will cause vibration during the operation of manipulators. Due to complicated dynamic coupling among manipulators, the rigid base and flexible appendages, it is very challenging to control the end-effector to track inertial trajectories, especially when the target states are constantly changing. This paper proposes a vibration suppression method for autonomous target capturing during the preimpact phase without controlling the base. Firstly, we derive the rigid-flexible coupling dynamics of a space robot system with flexible appendages. Then, the relationship among joint rates, elastic motion and the end-effector velocities is established by using the linear momentum and angular momentum conservation equations. Secondly, a closed-loop control system is designed based on the dynamic coupling model. And the control system is composed of target motion prediction, autonomous trajectory planning, energy-based joint controllers and so on. Thirdly, the energy-based joint control is detailed, which is proved to be stable by Lyapunov direct method. Finally, simulations of a planar space robot with two flexible appendages and a 3D space robot with single flexible appendage are provided to verify the effectiveness of the presented approach. The effectiveness of energy-based joint control for vibration suppression is verified by a single-degree-of-freedom space robot experimental system. The simulation and experimental results show that the space manipulator can successfully capture the moving target while suppressing the structure vibration. Highlights: The dynamics of a space robots with flexible appendages is derived. A vibration suppression method for autonomous target capturing is proposed. The energy-based joint control is proved to be stable by Lyapunov direct method. The simulations and experiment are presented to verify the method.